Potassium sources in covering fertilization on cotton i - Yield, fiber quality and economic analisys - Echer, Fábio Rafael [UNESP]; Foloni, José Salvador Simoneti; Creste, José Eduardo (Universidade Estadual de Londrina, 2009)
A field experiment was conducted in Sapezal, Mato Grosso state, Brazil, in 2007/2008, with the purpose of determining the effect of potassium sources on yield components, yield, fiber quality and economical aspects of cotton (Gossypium hirsutum L.). A randomized complete block experimental design was used, with five replications. The treatments consisted of application in covering, via soil, at rate of 100 kg ha-1 of K2O, in two split applications, of the sources KCl, K2SO4, KNO 3 and K2SO4.2MgSO4. The number of nodes, height, number of bolls in the superior third and the weight of boll in the medium third was higher with K2SO4.2MgSO4 than with KNO3 source. The potassium fertilizers did not influence the fiber revenue, but the fertilizing with K2SO4. 2MgSO4 source had higher cotton seed yield and lint yield, although the uniformity ratio of fibber and profitability were smaller in relation to K2SO4. The fibber agio index was higher with KNO3 source. The production cost was higher with K2SO 4.2MgSO4 source and in function of the smallest production cost, KCl source presented superior liquid revenue than other treatments.
Fontes de potássio na adubação de cobertura do algodoeiro I - Produtividade, qualidade de fibras e análise econômica
Keywords: Agio index; Gossypium hirsutum L; Mass of boll; Profitability